Consumer Trust and Purchase Decisions in Indian E-Commerce through Social Media Marketing Reviews and Influencer Endorsements - Anjali Janapalli; Harshini Wepuri; Gracy Jangir (Involvement International Journal of Business, 2026)
The rapid growth of Indian e-commerce has transformed consumer buying behavior, with social media becoming an important channel for product discovery, engagement, and purchase influence. However, the effectiveness of social media marketing largely depends on consumer trust, authentic reviews, and the credibility of influencer endorsements. This study aims to examine how social media marketing reviews and influencer endorsements shape consumer trust and purchase decisions in the Indian e-commerce market. This research employed a quantitative descriptive design using a structured online questionnaire distributed to 102 respondents with experience in social media and online shopping. Data were analyzed using descriptive statistics, frequency distribution, percentages, and cross-tabulation to identify dominant behavioral patterns and trust-related factors influencing purchase decisions. The results reveal that customer reviews and testimonials were the most influential factor (65.7%), followed by advertisements (44.1%), influencer recommendations (40.2%), brand posts (34.3%), and video demonstrations (22.5%). Moreover, 71.6% of respondents considered positive reviews as the strongest motivator for online purchases. However, 60.8% reported low trust in influencer recommendations and preferred genuine customer feedback. Trust issues (49.0%), unclear return policies (22.5%), payment security concerns (16.7%), and poor customer support (11.8%) were identified as major barriers. Many respondents also preferred cash on delivery as the safest payment option. The study concludes that while social media marketing effectively creates awareness and interest, consumer trust remains the central determinant of online purchase decisions. Authentic customer reviews are more persuasive than influencer endorsements alone. Businesses should therefore prioritize transparency, secure transactions, verified reviews, and customer-centered service strategies to strengthen trust and improve conversion performance in emerging digital markets.